Integrated co-creation process with multiple stakeholders in innovation networks - Sergio Takahashi; Vania Passarini Takahashi (Innovation & Management Review, 2022)
Purpose - The purpose of this paper is to study the organizational processes in co-creation with multiple stakeholders within the scope of innovation networks. It consists of analyzing the necessary adaptation of organizational processes and to structure a proposal of an integrated process. Design/methodology/approach - This paper is a review article, an analysis of relevant articles in the areas of co-creation with multiple stakeholders, innovation networks, dynamic capabilities and organizational aspects linked to network organization which reflect on the main differences by relating them to the relevant literature. Findings - Identification of related processes: Innovation development, knowledge integration/sharing, Co-evolution, Value Co-creation, Value Capture, Stakeholders capabilities, and elements of an integrated process in an innovation network. Originality/value - Proposition of an integrated co-creation process with multiple stakeholders in an innovation network based on dynamic capabilities with the elements of literature and an analysis of the model variables. This process makes it possible, before reconfiguring the network itself, to create and to define the Project in an integrated manner. They also promote an evolution in the commitment, in the relationship and in the sharing of knowledge among the stakeholders and in the anticipation and evaluation by the stakeholders.
Keywords: 650; Co-creation; Dynamic capabilities; Innovation network; Multiple stakeholders; Participation design